ANALYSIS OF THE NALO (NEEDS ANALYSIS, LEARNING, AND OUTPUT) EVALUATION FRAMEWORK FOR SENIOR HIGH SCHOOL PHYSICS LEARNING - Ryka Kaswati; Riyadi Riyadi; Yetti Supriyati (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The complexity of Physics learning in senior high schools requires an evaluation framework that not only measures learning outcomes but also identifies students' learning needs and the quality of instructional implementation. Existing evaluation models, such as CIPP and Hammond, have not comprehensively integrated these dimensions within a Physics-specific evaluation framework. This study aimed to develop the NALO Evaluation Model through a Systematic Literature Review. Relevant studies were identified from reputable international databases and analyzed using thematic synthesis to construct the conceptual dimensions and indicators of the proposed model. The findings revealed three interconnected evaluation components. The Needs Analysis component emphasizes diagnosing students' prior knowledge, misconceptions, cognitive and affective readiness, motivation, and learning context as the foundation for instructional planning. The Learning component evaluates teacher readiness, instructional planning, learning resources, teaching strategies, classroom interaction, formative assessment, and instructional organization to ensure effective implementation. The Output component extends evaluation beyond academic achievement to include conceptual understanding, scientific reasoning, science process skills, scientific attitudes, and twenty-first-century competencies comprising critical thinking, creativity, collaboration, and communication. The novelty of the NALO model lies in integrating these three components into a diagnostic and continuous evaluation framework that explains not only learning outcomes but also the underlying factors contributing to instructional effectiveness. The proposed model provides a comprehensive reference for evaluating and improving the quality of Physics learning in senior high schools.